Genetic admixture analysis of domesticated cattle - Freeman, Abigail Ruth (Trinity College (Dublin, Ireland). Department of Genetics, 2003)
Genetic admixture analysis of bovine hybrid zones was carried out through implementation of a variety of statistical and analytical methods. Population genetic analysis of microsatellite variation in seven cattle breeds from a selection of locations in South Asia and in sixteen cattle populations from West Africa are presented. These are the first such studies focusing within these areas, the former of which is one of the postulated centres of cattle domestication and the latter of which contains genetically important trypanotolerant Bos taurus cattle breeds. Genetic relationships among the breeds were examined and levels of diversity assessed. Admixture levels were estimated using multiple approaches including the systematic selection of population associated alleles and by a model-based Bayesian admixture analysis. These analyses show a Bos taurus influence in the Indian sub-continent, part of a gradation which stretches from Europe through the Near East towards India and which may be of ancient origin. The profound effect of admixture on West African cattle populations is also revealed, and these results highlight the importance of efforts to prevent further dilution of genetically unique trypanotolerant African taurine breeds by Bos itidicus cattle.
Keywords: Genetics, Ph.D.; Ph.D. Trinity College Dublin